PENGARUH KUALITAS LAYANAN DAN PERCEIVED VALUE TERHADAP LOYALITAS KONSUMEN YANG DIMEDIASI OLEH KEPUASAN KONSUMEN - Aditya Dwi Yulianto (University of Merdeka Malang, 2017)
The research aims to to assess more in-depth of the influence of relations the quality of services and perceived value of loyalty consumers that is mediated by satisfaction in the coffee shop Cak Wang in the city Jember .Sample in this research were 141 respondents and they are consumers the coffee shop Cak Wang in three location .As for methods used in research this is a nonprobabilitas sampling ) .Data collection use a method of surveying directly with an instrument kuisioner .To be analyzed uses the method and techniques analysis partial least square ( pls ). The results of the study showed that the direct effect between variable positive and significant.The influence of the quality of services loyalty greater than the quality of services to satisfaction, while the influence of perceived value to satisfaction most the largest and satisfaction quite influencing to loyalty. Good service quality will make a positive influence through customer satisfaction and the creation of customer loyalty, value are customers in conformity with expectation customers able to give the impression that good against customers so customers will buy again in the coffee shop cak wang. Management the coffee shop cak wang can increase satisfaction of consumers through improving its service overall as increase facilities needed customers in experience drink coffee in a tavern that would give satisfaction and the creation of loyalty customers. DOI : https://doi.org/10.26905/jbm.v4i2.1704